Validation of Lactate Minimum Power testing in cyclists - Dausin, C.; Carey, C. C.; Geuns, W.; Hespel, P. (Journal of Science and Cycling, 2019)
Introduction- Physiological profiling of elite endurance athletes shouldinclude determination maximal lactate steady state (MLSS) and VO2max. To improve determination of these two parameters in a single test session, we used the "lactate minimum power (LMP)" concept proposed by Tegtbur et al. in 1993. This procedure involves a maximal exercise bout to first substantially elevate blood lactate concentration, where after a submaximal incremental exercise bout, gradually shifts blood lactate balance from net lactate clearance to net accumulation. The nadir of the U-shaped blood lactate curve so obtained is believed to identify MLSS exercise intensity. The validity and accuracy to determine MLSS using LMP in endurance athletes is poorly documented. (Messias 2017) Furthermore, the effect of different maximal exercise bouts to elevate blood lactate has not yet been clarified. (Smith 2002)